A cross-sectional study of stretched penile length in boys from West Bengal, India - Ajitesh Roy; Rana Bhattacharjee; Partha P Chakraborty; Soumik Goswami; Kaushik Biswas; Pradip Mukhopadhyay; Subhankar Chowdhury (Indian Journal of Endocrinology and Metabolism, 2019)
Introduction: Short penile length is a commonly encountered problem in clinical practice. Detection of abnormal stretched penile length (SPL) warrants appropriate endocrine evaluation. Ethnicity-specific SPL data are required to detect these abnormalities. There is a dearth of such data in India. This study aims to establish normative values of SPL in boys from West Bengal. Materials and Methods: This is a cross-sectional study. SPL, testicular volume (TV), height/length, and weight were measured in 460 boys aged 1 to 13 years from the schools located at urban, suburban, and rural areas in the state of West Bengal, India. Similar data were collected from 36 healthy neonates within 1–3 days of full-term delivery at IPGME and R and SSKM Hospital, Kolkata, West Bengal, India. Results: The 5th percentile, median, and 95th percentile of SPL were 1.7, 2.0, and 2.7 cm for neonates; 3.5, 4.4, and 6.4 cm for the children aged 1 Y–2 Y 11 M; 4.0, 5.5, and 7.0 cm for the age group 3 Y–4 Y 11 M; 4.2, 6.0, and 7.2 cm for the age group 5 Y–6 Y 11 M; 4.3, 6.0, and 7.6 cm for the age group 7 Y–8 Y 11 M; 4.4, 6.5, and 9.0 cm for the age group 9 Y–10 Y 11 M; and 4.8, 7.0, and 11.0 cm for the age group 11 Y–12 Y 11 M, respectively. SPL showed significant positive correlation with TV [r = 0.365, P < 0.0005] and height of the children [r = 0.516, P < 0.0005], but not with BMI. Conclusion: Our study provides normative data of SPL in neonate and children aged 1 to 13 years from the eastern part of India. SPL value correlated positively with TV and height of children.